2016
DOI: 10.1021/acs.iecr.6b01376
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Au(III), Pt(IV), and Pd(II) Using Pyridylethyl-Containing Polymers: Chitosan Derivatives vs Synthetic Polymers

Abstract: The sorption properties of N-2-(2-pyridyl)­ethylpolyethylenimine (PEPEI), N-2-(2-pyridylethylpolyallylamine (PEPAA), and N-2-(2-pyridyl)­ethylchitosan (PEC), synthesized via the aza-Michael reaction with 2-vinylpyridine and cross-linked with epichlorohydrin, have been investigated. It was shown that sorption capacities toward Pd­(II) and Pt­(IV) changed in the order PEPEI > PEC > PEPAA, with the maximal capacity of 4.6 mmol Pd/g for PEPEI. All the derivatives showed comparable efficiencies in Pt­(IV) uptake, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The gold removal performance of the PmPD nanoparticles was compared with other materials reported regarding their respective capacity, affinity, and acidic level (Table S1). As shown in Figure f, the PmPD nanoparticles exhibited a high gold adsorption capacity (2063.09 mg/g) and an extremely high-affinity K d (1.67 × 10 7 mL/g), outperforming most materials previously reported, including POSS-2, PEC, and CuS 38 nanoparticles. The exceptional selectivity of PmPD nanoparticles to gold can be attributed to the anion existing species of gold, which is different from other competing metals that mainly exist in cationic form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gold removal performance of the PmPD nanoparticles was compared with other materials reported regarding their respective capacity, affinity, and acidic level (Table S1). As shown in Figure f, the PmPD nanoparticles exhibited a high gold adsorption capacity (2063.09 mg/g) and an extremely high-affinity K d (1.67 × 10 7 mL/g), outperforming most materials previously reported, including POSS-2, PEC, and CuS 38 nanoparticles. The exceptional selectivity of PmPD nanoparticles to gold can be attributed to the anion existing species of gold, which is different from other competing metals that mainly exist in cationic form.…”
Section: Resultsmentioning
confidence: 99%
“…Adsorption characteristics of PmPD particles for Au­(III) removal ([Au­(III)] 0 = 40 mg/L): (a) effect of pH on the Au adsorption rate; (b) isotherm of Au­(III) adsorption by PmPD particles fitted by Langmuir model (solid line); (c) zeta potential measurements of PmPD at pH ranging from 2 to 11; (d) removal of various cations by PmPD particles in a mixture containing different ions at equal concentration (50 mg/L); (e) distribution coefficients ( K d ) of various cation species; and (f) comparison of maximum adsorption capacities ( q max ) and distribution coefficient ( K d ) of PmPD particles with those of other reported adsorbents in the literature. …”
Section: Resultsmentioning
confidence: 99%
“…Although the results were not exciting but further modification can lead to efficient material for the purpose. [91] Metal ion plays a crucial role in designing biologically active compounds, and it has been observed that changing central metal ion can drastically increase applicability in many cases. [92] Metal complexes particularly those containing Pd, Pt Au and Cu ions and Nligands are very promising against various human ailments including cancers.…”
Section: Coordination Compounds For Biological Applicationsmentioning
confidence: 99%
“…In particular, polymer-based adsorbents have been extensively employed owing to their high adsorption capacity, scalability, and chemical tunability 16 . Commercially available amine-functionalized polymers, such as branched poly(ethyleneimine) (bPEI) and poly(allylamine hydrochloride) (PAAm), are commonly used to fabricate PM adsorbents because of their high electrostatic affinity to PM ions 17 20 . However, these polymers cannot be used as standalone adsorbents because of their small particle size, which hinders their collection.…”
Section: Introductionmentioning
confidence: 99%